Gender and land degradation neutrality: A cross‐country analysis to support more equitable practices. (24th May 2019) - Okpara, Uche T.; Stringer, Lindsay C.; Akhtar‐Schuster, Mariam
Abstract: Women and men have unequal opportunities to address land degradation. Although adoption of Sustainable Development Goal target 15.3 leads the world to "strive towards land degradation neutrality (LDN)" by 2030, gender concerns are sparsely considered in LDN programming to date. To achieve LDN in regions with deeply entrenched sociocultural norms requires gender responsiveness, accounting for the varied gender components of land degradation. This paper identifies innovative entry points for, and benefits of, integrating gender issues into LDN, as well as the risks of gender inaction. Assessment of the literature on the links between gender and land reveals land degradation is gendered and closely tied to gender biases in land rights, access to resources and incentives, opportunities to participate in decision making, and the distribution of costs/benefits of projects targeting land improvement. Analysis of selected LDN‐related projects shows that interventions seem to target gender biases by engaging: women's groups that are locally recognised as change agents in driving inclusiveness and gender specialists to coordinate gender mainstreaming activities. Entry points for gender‐responsive LDN are identified, including interventions that merge LDN gender plans with existing gender schemes at local and global levels, enable gender‐sensitive early warning systems, and narrow gender disparities and safeguard women's land rights through gender‐sensitive LDN financing mechanisms. Gender‐responsive LDN is one of several avenues to support growing international efforts to promote gender equality and female empowerment, alongside movement towards a future where more balanced relations ensure women and men can interact with and care for land in more equitable and nonhierarchical ways.